A review of the hyperiidean amphipod family Brachyscelidae Stephensen, 1923 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2021)
This is the first comprehensive taxonomic review of the family Brachyscelidae. The family is currently mono-generic following the review of Zeidler (2016). There are 17 nominal species referable to the genus Brachyscelus in the literature including two old references to species that most likely represent species of Brachyscelus. However, most are regarded junior synonyms of the two better known species B. crusculum Spence Bate, 1861 and B. globiceps (Claus, 1879). The taxonomic status of all nominal species was re-determined by the examination of extant type material or from the original literature reference if type material could not be found. In conclusion, five species of Brachyscelus are recognized as valid. Brachyscelus crusculum is the most common and widespread species and is most often recorded in the literature, but it is likely that some of these literature records are erroneous because other species have been confused with it in the past. The other species recognized are B. globiceps, B. macrocephalus Stephensen, 1925, B. rapacoides Stephensen, 1925 and B. rapax (Claus, 1871). Brachyscelus globiceps and B. macrocephalus are well established species and the validity of B. rapacoides was recently confirmed by Zeidler et al. (2018) but the validity of B. rapax is difficult to determine because type material could not be found and the original description by Claus (1871) and later figure (Claus 1887) are very inadequate. However, the species is tentatively recognized here based on several specimens which are most likely this species as according to Claus (1871, 1887). Brachyscelus is widely distributed in tropical and warm-temperate regions of the world’s oceans including the Mediterranean Sea. Species are preferentially associated with medusae and to a lesser extent with salps.